Toward a Critical Theory Of Female Criminality - Curry Thompson, Ann (1976)
Twentieth-century theories about female criminality are the weakest link in conventional criminology, representing the most conservative and unscientific thinking about human nature and social organization. Traditional thinking about female criminality reflects the general inability of conventional theorists to examine categories of sex, race, and class oppression as determined by the basic social structure of a particular society and as they relate to deviance and crime. The result has been that female deviance has been analyzed solely in light of assumptions about women's biological nature. Whether there is indeed something distinctive about female crime which can be explained apart from a more general theory is problematic. Nevertheless, the recent resurgence of a radical materialist criminology, which roots the problem of crime in the underlying conditions of social production, suggests a methodology for analyzing the relationship between female crime and the rate of female participation in the labor force in advanced capitalist society